Facile Preparation of Self‐Sensitized FOX‐7 with Uniform Pores by Heat Treatment. Issue 2 (18th March 2014) - Li, Tingting; Li, Rui; Nie, Fude; Wang, Jun; Huang, Weigang; Yang, Guangcheng
Abstract Self‐sensitized FOX‐7 (1, 1‐diamino‐2, 2‐dinitroethylene) was prepared by a facile heat treatment process near the decomposition temperature. Field emission scanning electron microscopy (FE‐SEM) shows the self‐sensitized FOX‐7 becomes multiple layers and porous after heat treatment. N2 adsorbance measurements revealed that its specific surface area (6.754 m2 g−1) is 20 times of the area of expanded ammonium nitrate. The SAXS tests further indicate the existence of a large amount of voids in self‐sensitized FOX‐7 and the pore size is about 30 nm, belonging to mesopore (2.0–50 nm). Based on the analysis of X‐ray powder diffraction (XRD), the self‐sensitized porous FOX‐7 consists of α‐phase and a spot of γ‐phase. The TG‐DSC results show that the self‐sensitized FOX‐7 exhibits excellent thermal stability. The impact, frication and electrostatic spark sensitivities of self‐sensitized FOX‐7 also have considerable enhancement. This new method provides a promising route for exploring new green primary explosive replacements.